Efficacy and safety of guselkumab in patients with active psoriatic arthritis who are inadequate responders to tumour necrosis factor inhibitors: results through one year of a phase IIIb, randomised, controlled study (COSMOS) - Coates, Laura C.; Gossec, Laure; Theander, Elke; Bergmans, Paul; Neuhold, Marlies; Karyekar, Chetan S.; Shawi, May; Noel, Wim; Schett, Georg; Mcinnes, Iain B. (Annals of the Rheumatic Diseases, 2021)
Objective To evaluate efficacy and safety of guselkumab, an anti-interleukin-23p19-subunit antibody, in patients with psoriatic arthritis (PsA) with prior inadequate response (IR) to tumour necrosis factor inhibitors (TNFi).
CRIS-Team WoS Importer:2021-12-03